Human Potential in the AI Era: Strategies for Cultivating Exceptional Talent - Muhammad Rizal; Novrizal Novrizal; Dadang Irawan; Mia Christy Patricia (International Forum of Researchers and Lecturers, 2022)
This research aims to explore strategies for cultivating exceptional talent in the era of artificial intelligence (AI). The study employs a mixed-method approach, integrating interviews, surveys, and case studies to gather comprehensive data. The sample selection includes individuals from various industries known for fostering talent development, such as technology, education, and business. Through thematic analysis, the collected data are systematically examined to identify recurring patterns, emerging themes, and innovative practices in talent cultivation. Results reveal multifaceted strategies encompassing personalized learning, mentorship programs, continuous feedback mechanisms, and proactive skill development initiatives. Furthermore, the study highlights the significance of human-centric approaches in leveraging AI technologies to enhance talent development efforts. The findings contribute to a deeper understanding of how organizations can harness human potential effectively amidst technological advancements, paving the way for sustainable talent management practices in the AI era.